2009
DOI: 10.3136/fstr.15.525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Adlay Leaves on 2,4,6-trinitro-1-chlorobenzene-induced Chronic Dermatitis in Mice

Abstract: Diets containing either dehulled adlay seeds or young adlay leaves were administered to mice. The hapten 2,4,6-trinitro-1-chlorobenzene (TNCB) was applied to the right ear of mice daily for 28 days to generate a model of chronic dermatitis. The thickness of the right ear was measured to evaluate the pathology of allergy. The symptoms of mice fed diet containing adlay leaves were reduced. The serum IgE levels of mice belonging to both adlay groups were significantly lower than the control group. The IFN-γ level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Pharmacological research has demonstrated a wide spectrum of biological activities of CS, including anti-inflammatory [6][7][8], anti-allergic [9], antioxidant [10][11][12], and antitumor activities [1]. Several studies using animal models have demonstrated that CS exerts anti-inflammatory and anti-allergic effects by regulating pro-inflammatory cytokine expression and suppressing cyclooxygenase 2 (COX-2) and prostaglandin E 2 (PGE2) production [13,14]. CS is widely used as a therapeutic agent for inflammatory skin disorders, such as atopic dermatitis [15,16] and acute radiation dermatitis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological research has demonstrated a wide spectrum of biological activities of CS, including anti-inflammatory [6][7][8], anti-allergic [9], antioxidant [10][11][12], and antitumor activities [1]. Several studies using animal models have demonstrated that CS exerts anti-inflammatory and anti-allergic effects by regulating pro-inflammatory cytokine expression and suppressing cyclooxygenase 2 (COX-2) and prostaglandin E 2 (PGE2) production [13,14]. CS is widely used as a therapeutic agent for inflammatory skin disorders, such as atopic dermatitis [15,16] and acute radiation dermatitis [17].…”
Section: Introductionmentioning
confidence: 99%